Development aid taxation act amendment - Hans Günther Meissner (Intereconomics, 1972)
One of the important tasks which the new Federal Government will have to tackle during 1973 is the amendment of the Entwicklungshilfe-Steuergesetz (Development Aid Taxation Act). The following article reviews the aims of the Act and suggests modifications necessary for improving its effectiveness.
Keywords: 330; Germany